The effects of heat stress on hydration status, physiological strain, and cognitive function in humans - Deming, Nathan Joshua, author; Dinenno, Frank A., advisor; Richards, Jennifer C., advisor; Maresh, Ryan W., committee member; Young, Brian A., committee member; Broussard, Josiane L., committee member (Colorado State University. Libraries, 2021)
The following dissertation is comprised of a series of experiments with the overall aim of determining the change in hydration status, cardiovascular and thermal strain (i.e. physiological strain), and cognitive function of healthy individuals in response to bouts of both short (<60 minutes) and long-duration (>120 minutes) passive and active heat stress. Increasing core temperatures that occur from the imbalance of heat gain to heat loss, termed uncompensable heat stress, is the primary reason for succumbing to heat related illnesses in many different athletic and occupational settings. However, appreciating the differences in the effects of short and long-duration passive and active heat stress on the hydration status, physiological strain, and cognitive function in humans, have yet to be fully explained in the literature. Understanding the differences in these physiological metrics, especially cognitive function, could lend itself to the establishment of specific techniques and treatments (clinically and field-based) to mitigate physical and cognitive decline following bouts of both short or long-duration heat stress. To better uncover these physiological changes, we simulated active and passive heat stress conditions within a controlled laboratory environment, using steady-state workloads, ad-libitum drinking patterns, and a set temperature and relative humidity to reduce fluctuating environmental and working conditions that could adversely influence primary outcome variables. We hypothesized that short and long-duration bouts of heat stress, both active and passive, will (1) decrease measures of hydration status; (2) increase markers of physiological strain; and (3) decrease measures of cognitive function. Furthermore, we hypothesize that the declines in cognitive function will be unaffected due to fluid supplementation type and primarily occur secondary to hyperventilation-induced hypocapnia reducing global cerebral blood flow through the internal carotid artery. The primary finding of this dissertation is that cognitive function declines following long-duration bouts of heat stress and that this degradation is independent to the type of heat stress (passive or active) or the variety of fluid supplementation. However, contrary to our hypothesis, this decline in cognitive function, although associated with decreases in global cerebral blood flow that are stimulated by hyperventilation-induced hypocapnia, can be significantly blunted if individuals consume fluids supplemented with exogenous glucose.
Keywords: cerebral blood flow; glucose supplementation; thermoregulation; cognitive function; carotid chemoreceptors; physiological strain